The exploration of a potential new pamor pattern / Azhar A. Aziz ... [et al.] - A. Aziz, Azhar; Abdull Manan, Emilia; Abdul Manan, Mohd Masdi; Shamsuddin, Rozita (2015)
The value of the kris often refers to the patterns created from pamor. Pamor is the mixture of alloy which forms a unique pattern that is obtained by welding together wrought iron, nickel and certain kind of metals into one blade. Pamor is the most striking and interesting feature in the existence of a kris and one of the Malaysian Heritage that is facing a decline nowadays. This study is to create new pamor pattern with its own expression of the art form influenced by its locality, history and cultural diversity. The study focuses on the method of simplification in creating traditional Malaysian pamor pattern. The position of pamor in art and culture is interrelated to the issues of cultural development in the country. This research explores the preservation of pamor as an integral part of the metal and kris as cultural heritage. It also compiles traditional Malaysia pamor pattern with their design characteristics that are identified and documented the pamor making process. The data collection will then used as the foundation in creating potential new pamor patterns and the finding includes the pattern making process and the pattern appears. Qualitative research method is considered appropriate in analysing and viewing the result which will be achieved as it is more meaningful, accurate and rich with significant information (Miles and Huberman, 1994).